Shades of Meaning: Shadows in Medieval Manuscript Illumination - DeLuca, Dominique, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
Are there shadows in medieval art? Studies on the role of shadows in art history have either glanced over or ignored the medieval period, yet people of the Middle Ages certainly saw and thought about shadows and recorded their ideas about these phenomena in texts and images. This book examines references to shadows in science, religion, and folklore of the Middle Ages. Through the lens of fifteenth-century manuscript painting, it investigates visual, metaphorical, and supernatural shadows in art to discover what shadows meant to the medieval viewer.